Medical cannabis and cannabinoids for impaired sleep: a systematic review and meta-analysis of randomized clinical trials. Issue 2 (21st September 2021) - AminiLari, Mahmood; Wang, Li; Neumark, Samuel; Adli, Taranah; Couban, Rachel J; Giangregorio, Aidan; Carney, Colleen E; Busse, Jason W
Abstract: Study Objectives: We conducted a systematic review to explore the effectiveness of medical cannabis for impaired sleep. Methods: We searched MEDLINE, EMBASE, CENTRAL, and PsychINFO to January 2021 for randomized trials of medical cannabis or cannabinoids for impaired sleep vs. any non-cannabis control. When possible, we pooled effect estimates for all patient-important sleep-related outcomes and used the GRADE approach to appraise the certainty of evidence. Results: Thirty-nine trials (5100 patients) were eligible for review, of which 38 evaluated oral cannabinoids and 1 administered inhaled cannabis. The median follow-up was 35 days, and most trials (33 of 39) enrolled patients living with chronic cancer or noncancer chronic pain. Among patients with chronic pain, moderate certainty evidence found that medical cannabis probably results in a small improvement in sleep quality versus placebo (modeled risk difference [RD] for achieving the minimally important difference [MID], 8% [95% CI, 3 to 12]). Moderate to high certainty evidence shows that medical cannabis vs. placebo results in a small improvement in sleep disturbance for chronic non-cancer pain (modeled RD for achieving the MID, 19% [95% CI, 11 to 28]) and a very small improvement in sleep disturbance for chronic cancer pain (weighted mean difference of –0.19 cm [95%CI, –0.36 to –0.03 cm]; interaction p = .03). Moderate to high certainty evidence shows medical cannabis, versus placebo, results in a substantial increase in the risk of dizziness (RD 29% [95%CI, 16 to 50], for trials with ≥3 months follow-up), and a small increase in the risk of somnolence, dry mouth, fatigue, and nausea (RDs ranged from 6% to 10%). Conclusion: Medical cannabis and cannabinoids may improve impaired sleep among people living with chronic pain, but the magnitude of benefit is likely small.